Association of domain-specific physical activity and cardiorespiratory fitness with all-cause and cause-specific mortality in two population-based cohort studies. Issue 1 (December 2018) - Bahls, Martin; Groß, Stefan; Baumeister, Sebastian; Völzke, Henry; Gläser, Sven; Ewert, Ralf; Markus, Marcello; Medenwald, Daniel; Kluttig, Alexander; Felix, Stephan; Dörr, Marcus
Abstract Physical activity (PA) reduces the risk for mortality. Whether the beneficial effects of PA are domain specific is unclear. We associated leisure time (LTPA), sports (SPA) and work (WPA) related PA and cardiorespiratory fitness (CRF) with all-cause mortality in two German population-based cohorts. We used data of the Study of Health in Pomerania (SHIP, n = 2, 935, median age 53; 48% male) and the Cardiovascular Disease, Living and Ageing in Halle study (CARLA, n = 1, 776, median age 64 and 54% male). Mortality was determined after a median follow-up of 8.2 years in SHIP (n = 332) and 11.5 years in CARLA (n = 409). LTPA (SHIP: hazard ratio [HR] per standard deviation [SD] 0.82 95%-CI 0.73 to 0.91 and CARLA: HR per SD 0.70: 95%-CI 0.59 to 0.82) and SPA (SHIP: HR per SD 0.80 95%-CI 0.71 to 0.91 and CARLA: HR per SD 0.70 95%-CI 0.60 to 0.82) but not WPA were inversely associated with all-cause mortality. In a subsample CRF was inversely related to mortality and positively to LTPA and sports SPA. No association was found for WPA. Our results may suggest that the inverse association between PA and mortality are partly influenced by higher CRF.